2016
DOI: 10.1080/15564894.2016.1204385
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Columbian Fishing on the Coast of the Atacama Desert, Northern Chile: An Investigation of Fish Size and Species Distribution Using Otoliths From Camarones Punta Norte and Caleta Vitor

Abstract: The bountiful marine resources of the northern Chilean coast offset the extreme aridity of the Atacama Desert in pre-Columbian times, underwriting permanent human occupation, and providing the basis for a long tradition of marine subsistence. We analysed fish otoliths (n=549) recovered from the sites of Camarones Punta Norte (occupied ca 7000-5000 years ago) and Caleta Vitor (occupied ca 9500-300 years ago) to investigate species distribution and changes over time. We also estimated the size of the fish based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…This area was selected for this study as it spans over 9,000 years of prehistoric occupation and offers welldated archeological records (Table 2; Figure 2). Neither has it been affected by urban development, which makes it a superb study area for our ongoing interdisciplinary research into the prehistory of the Atacama Desert (Roberts et al, 2013;Swift et al, 2015;Bland et al, 2016;Disspain et al, 2016;Latorre et al, 2017). Archaeological sites at Caleta Vitor are extensive and cover an area of at least 525,000 m 2 .…”
Section: Methodsmentioning
confidence: 99%
“…This area was selected for this study as it spans over 9,000 years of prehistoric occupation and offers welldated archeological records (Table 2; Figure 2). Neither has it been affected by urban development, which makes it a superb study area for our ongoing interdisciplinary research into the prehistory of the Atacama Desert (Roberts et al, 2013;Swift et al, 2015;Bland et al, 2016;Disspain et al, 2016;Latorre et al, 2017). Archaeological sites at Caleta Vitor are extensive and cover an area of at least 525,000 m 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Their focus on the marine resource reflected the abundance of fish in coastal waters due to seasonal upwelling (e.g. Disspain et al, : 429; Standen et al, : 163), a mechanism that also causes an abundance of fish stocks off the coast of Oman (Cleuziou & Tosi, : 14; Sreeush et al, ). Similarly, Aboriginal groups in the western desert of Australia are known to utilise different environmental zones in the landscape, including river fish and wild game, on a seasonal basis (Cane, ).…”
Section: Discussionmentioning
confidence: 99%
“…This highly productive ecosystem, coupled with terrestrial resources yielded by the wetland provides an abundance and variety of terrestrial and marine fauna and flora, all within the context of an extreme hyperarid environment (Herreros 2011;Fariña and Camaño 2012;Hernández et al 2014;González and Molina 2017;Latorre et al 2017). Interdisciplinary analyses of Caleta Vitor shell middens show long-term subsistence systems and socio-cultural structures based on terrestrial and maritime resources since the beginning of human occupation early in the Holocene (Roberts et al 2013;Carter 2016;Disspain et al 2016b;Santoro et al 2017;Martens and Cameron 2019;Santoro et al 2020).…”
Section: Recovery Methods Of Fish Remains In Caleta Vitormentioning
confidence: 99%
“…In this regard, Martens and Cameron (2019) suggest its use, among other activities, as fishing nets. Even though the authors and other researchers (Carter 2016;Disspain et al 2016b) have suggested the use of these fishing strategies for small (sardines and anchovetas) and middle size fish species (Sciaenidae), there is no in-depth discussion about taxonomical distribution and variation through time. Furthermore, discussion of methodologies for field and lab recovery of fish remains as well as their analytical procedures is also lacking.…”
Section: Fishing Along the Atacama Desert Coast Northern Chile: The mentioning
confidence: 99%
See 1 more Smart Citation